ANALISIS INVESTASI USAHATANI KEDELAI VARIETAS TANGGAMUS DI KABUPATEN GORONTALO - Zulkifli Mantau (AGRI-SOSIOEKONOMI, 2015)
The increase of soybeans  world price was causing of a domino effect for the Indonesian’s soybeans. Meanwhile, soybean productivity at the farm level is still low ( 1.3 t / ha ) with a range from 0.6 to 2.0 t / ha. In additional, the production technology can able to result of 1.7 to 3.2 t / ha . To solve these problems, It needs to planted the soybean that have a high productivity and efficient technically and economically.  The aims of this research are to find the investement feasibility of soybean farming (Tanggamus var.) at Puncak Village, Gorontalo District with benefit cost analysis approach (3 years projection). This research conducted at Puncak Village, Pulubala sub district, Gorontalo District. The datas was a primary observation data in the field, especially the data of soybeans farming activities for 2 seasons (1 year).  Analysis method use a benefit cost analysis. The analysis use a financial price (actual price) in the cost factors. The result showed that Net Present Value (NPV) (12%) Rp 10 269 643, Internal Rate of Return (IRR) 97.21%, Net Benefit Cost ratio (Net B/C) 2.64 and Payback periodh (PBP) 9 months or 0.7 year or 2 planted seasons.